Study on the anisotropic characteristics of mechanical properties and energy evolution in layered phyllite - Luhai Chen; Baoping Xi; Na Zhao; Yunsheng Dong; Shuixin He; Keliu Liu; Pengli Gao; Jin Xie (PLoS ONE, 2026)
To investigate the anisotropic characteristics of the mechanical properties and energy evolution in layered rock masses, conventional triaxial compression tests were carried out on layered phyllite specimens with different bedding angles (0°, 30°, 45°, 60°, and 90°). Based on the test results and the law of energy conservation, the anisotropic mechanical behavior and energy evolution were analyzed. The results show that the deformation characteristics of layered phyllite under different confining pressures and bedding angles are similar, with overall brittle failure. The bedding angle and confining pressure significantly affect its dilation behavior. The peak strength, elastic modulus, internal friction angle, and cohesion of the layered phyllite exhibit a “U”-shaped distribution, first decreasing and then increasing, with significant anisotropy. However, the anisotropy of the Poisson’s ratio is not pronounced. The increase in confining pressure enhances the mechanical properties of the layered phyllite and reduces its anisotropic behavior. The failure modes of the layered phyllite primarily include shear failure along the bedding planes and tensile splitting failure along the bedding planes, both showing significant bedding and confining pressure effects. The energy evolution of layered phyllite with different bedding angles is similar. The peak total absorption energy ( U p ), peak elastic strain energy ( U p e ), and peak dissipated energy ( U p d ) first decrease and then increase as the bedding angle increases. Additionally, these energies exhibit a nonlinear increase with increasing confining pressure.